ANALYSIS OF DIGLOSSIA'S POSITIVE ATTITUDE IN IMPROVING ACADEMIC PERFORMANCE TITLE - Deisy Permata Nurfaizar Sari; Trisa Nurfitri; Ichsan Fauzi Rachman (Media Inovasi Pendidikan dan Publikasi, 2024)
This research was motivated by the existence of two different types of language which were considered obstacles to students' education and academic achievement. This research aims to reveal the positive attitude of diglossia in improving student academic achievement. The type of research method used is a qualitative approach with literature study data collection techniques. This technique is carried out by searching, reading and analyzing previous written sources. The research subjects are